PENGEMBANGAN MEDIA MONOKERABU PADA PEMBELAJARAN TEMA INDAHNYA KERAGAMAN DI NEGERIKU KELAS IV - Widya Utami; Dara Fitrah Dwi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study aims to develop MONOKEBU learning media based on the theme "Beautiful Diversity of My Country" with attractive design, diverse menu display, and clear, accurate, and detailed material. This learning media was then evaluated by two teams of validators consisting of media experts and material experts. The evaluation results showed that MONOKEBU learning media received an average score of 86,6% from media experts and an average score of 95% from material experts, with the criteria "very feasible" to be used and developed. Student response to MONOKEBU learning media is also very positive, with a percentage of 92% stating that the media is very interesting. Students gave feedback that MONOKEBU learning media was able to attract their attention, increase interest in learning, and use simple and easy-to-understand language. In addition, students' pretest and post-test results showed significant differences, with the total post-test score increasing from 1380 to 1760, and the average score increasing from 69 to 88. Based on the results of this study, it can be concluded that the development of MONOKEBU learning media succeeded in creating a product that is feasible and effective to use in the learning process. MONOKEBU learning media is able to attract student interest, increase understanding, and obtain better learning outcomes. Thus, MONOKEBU learning media can be used as an effective solution in improving the quality of learning with an interactive approach.